The Efficacy of Massage on Preterm Infants: A Meta-Analysis - Wang, Li; He, Jun Li; Zhang, Xian Hong (American Journal of Perinatology, 2013)
Objective To determine whether massage could help preterm infants improve weight gain, discharge from the hospital earlier, and promote the neurobehavioral development, a meta-analysis was conducted.Study Design MEDLINE, Embase, CINAHL, Dissertation Abstracts, and the Cochrane Library were searched up to January 2012. There were no language restrictions.Results In all, 611 articles were retrieved and 17 studies were eligible. Massage intervention improved daily weight gain by 5.32 g (95% confidence interval [CI] 4.15, 6.49, p < 0.00001) and reduced length of stay by 4.41 days (95% CI 2.81, 6.02, p < 0.00001). No significant differences yielded on the scores of Neonatal Behavioral Assessment Scale.Conclusion Massage therapy may be a safe and cost-effective practice to improve weight gain and decrease the hospital stay of clinically stable preterm infants. However, the association between massage and neurobehavioral development is still elusive. Future investigations with a larger sample size and strict protocol are required to confirm the effects of massage on the preterm infants.
Keywords: massage; preterm infant; weight gain; hospital stay; NBAS